Transformational leadership: Effects on workplace spirituality, emotional intelligence, and organizational citizenship behaviours / Nauman Majeed - Nauman , Majeed (2018)
Organizational Citizenship Behaviour (OCB) of the organizational members is becoming progressively vital and understanding how OCB works in organizations is an important issue of investigation equally for researchers and practitioners. OCB is recognized as extra-role behaviours performed beyond the stated job requirements. Study of OCB in academicians and in educational institutions is of high value that definitely needs attention. Leadership and Organizational Citizenship Behaviour (OCB) stayed at the pinnacle in the arena of organizational behaviour research since decades and has attained significant consideration of scholars pursuing to define multifaceted dynamics of leadership and their influence on follower’s behaviour at work. This study aims to investigate the relationship between Transformational Leadership (TL) and OCB of academicians in public sector higher education institutions in Pakistan. Despite the importance of influencing subordinates for leadership effectiveness, leaders in universities are usually not aware of their leadership style to influence and motivate employees, bring about extra effort and to increase the performances of the universities. This study examines how transformational leadership influences citizenship behaviours through rarely used dimensions OCBO (Organization) & OCBI (Individual) directly and indirectly through exploring the mediating role of Workplace Spirituality (WS) and Emotional Intelligence (EI). The current study develops an integrated research model to investigate the proposed relationships and how the variables influence the dependent variable. Two theoretical models social exchange and transformational leadership were adopted and integrated to describe the causal linkages between the independent and dependent variables. Subsequently, twelve hypotheses were developed and tested based on the integrated research model. A questionnaire that reflects the research constructs is developed to collect the primary data for this study. The data were collected from 408 academicians employed in eight public sector universities of Pakistan. Since this study is quantitative with a deductive approach, it employs Partial Least Squares – Structural Equation Modelling (PLS-SEM) to validate and confirm research model by testing the relationships that were hypothesized. This study focuses on a second-order hierarchical latent variable model that include reflective - formative relationships. In this study typology of (second-order), a hierarchical latent variable model with a focus on the repeated indicator approach is used. The findings of this study provide empirical evidence for the significant influence of workplace spirituality and emotional intelligence on the relationship between transformational leadership and OCB. The PLS results showed that all evaluation factors have statistically significant impact on OCBO and OCBI except the relationship between EI and OCBI and whether EI mediates the relationship between transformational leadership and OCBI was found not to be significant. Out of twelve hypotheses, ten are supported except two. The findings make a significant contribution to organizational behaviour and leadership literature and propose that organizations should implement practices that help in building the climate of OCB in organizations. Furthermore, the study findings approve the influence of workplace spirituality and emotional intelligence on the relationship between transformational leadership and OCB. Finally, various study implications, limitations, and future research are highlighted.